"Playing the system": Structural factors potentiating mental health stigma, challenging awareness, and creating barriers to care for Canadian public safety personnel. (May 2020) - Ricciardelli, Rosemary; Carleton, R Nicholas; Mooney, Taylor; Cramm, Heidi
There are growing concerns about the impact of public safety work on the mental health of public safety personnel; as such, we explored systemic and individual factors that might dissuade public safety personnel from seeking care. Public safety personnel barriers to care-seeking include the stigma associated with mental disorders and frequent reports of insufficient access to care. To better understand barriers to care-seeking, we thematically analyzed the optional open-ended final comments provided by over 828 Canadian public safety personnel as part of a larger online survey designed to assess the prevalence of mental disorders among public safety personnel. Our results indicated that systematic processes may have (1) shaped public safety personnel decisions for care-seeking, (2) influenced how care-seekers were viewed by their colleagues, and (3) encouraged under-awareness of personal mental health needs. We described how public safety personnel who do seek care may be viewed by others; in particular, we identified widespread participant suspicion that coworkers who took the time to address their mental health needs were "abusing the system." We explored what constitutes "abusing the system" and how organizational structures—systematic processes within different public safety organizations—might facilitate such notions of abuse. We found that understaffing may increase scrutiny of injured public safety personnel by those left to manage the additional burden; in addition, cynicism and unacknowledged structural stigma may emerge, preventing the other public safety personnel from identifying their mental health needs and seeking help. Finally, we discuss how system-level stigma can be potentiated by fiscal constraints when public safety personnel take any leave of absence, inadvertently contributing to an organizational culture wherein help-seeking for employment-related mental health concerns becomes unacceptable. Implications for public safety personnel training and future research needs are discussed.